2019
DOI: 10.3389/fonc.2019.01262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Mixed Gestational Trophoblastic Neoplasia: A Study of 16 Cases and a Review of the Literature

Abstract: Objective: Mixed gestational trophoblastic neoplasia (GTN) is a rare occurrence that refers to the coexistence of choriocarcinoma and/or placental site trophoblastic tumor and/or epithelioid trophoblastic tumor. The diagnosis and management of mixed GTN are challenging. We investigated the clinicopathological characteristics, diagnoses, treatments, and outcomes of patients with mixed GTN.Materials and Methods: The medical records and pathological sections of 16 patients with mixed GTN who were treated at Pekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Chemo-resistance can be due to mixed gestational trophoblastic neoplasia (GTN) which is a rare occurrence that refers to the coexistence of choriocarcinoma and/or placental site trophoblastic tumor and/or epithelioid trophoblastic tumor. Diagnosis and management of mixed GTN are challenging as was mentioned by Kong, et al [28]. Prediction of GTN and its assessment by serum β-hCG levels, slope or 2 weeks readings [29]- [35], all need time, while in the current study a post-evacuation single Doppler reading is suggested as a non invasive predictor for GTN.…”
Section: Discussionmentioning
confidence: 66%
“…Chemo-resistance can be due to mixed gestational trophoblastic neoplasia (GTN) which is a rare occurrence that refers to the coexistence of choriocarcinoma and/or placental site trophoblastic tumor and/or epithelioid trophoblastic tumor. Diagnosis and management of mixed GTN are challenging as was mentioned by Kong, et al [28]. Prediction of GTN and its assessment by serum β-hCG levels, slope or 2 weeks readings [29]- [35], all need time, while in the current study a post-evacuation single Doppler reading is suggested as a non invasive predictor for GTN.…”
Section: Discussionmentioning
confidence: 66%
“…Programmed cell death 1 (PD-1) is a transmembrane glycoprotein of the Ig superfamily that acts as a T-cell coinhibitory receptor ( 15 ). Blockade of the PD-1 pathway activity with antibodies against PD-1 has been investigated in choriocarcinoma with encouraging results ( 16 , 17 ). Toripalimab as a novel PD-1 inhibitor has presented its promising efficacy in patients who developed chemo-refractory carcinomas ( 12 , 18 ), whereas no study has ever investigated the effectiveness of toripalimab in chemo-resistant choriocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The time between the previous pregnancy and onset of the disease suggests that these tumor components may originate from metastasis during pregnancy, surgical implantation and the small amount of left ovary found in the history of partial hydatidiform mole. Epithelioid trophoblasts also increase the probability of ETT recurrence and metastasis[ 5 - 8 ]. ETT usually manifests as abnormal vaginal bleeding with serum β-hCG level < 2500 U/L; the serum β-hCG, in this case, was initially 12878 U/L, and transvaginal ultrasound indicated abnormal echoes in the appendages[ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid trophoblasts also increase the probability of ETT recurrence and metastasis[ 5 - 8 ]. ETT usually manifests as abnormal vaginal bleeding with serum β-hCG level < 2500 U/L; the serum β-hCG, in this case, was initially 12878 U/L, and transvaginal ultrasound indicated abnormal echoes in the appendages[ 7 , 8 ]. The above clinical manifestations, serum β-hCG and B-ultrasound results are similar to those of ectopic pregnancy[ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation